Kaifiyat Mujadalah: Metode Dakwah Berbasis Argumentasi - Aep Kusnawan (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2002)
So far, kaifiyat mu]adalah remains unknown as a term, albeit this term has come to Indonesia since centuries and even found in Alquran itself (QS. 16: 125). As a method of dakwah, mujadalah means a way or strategy to call for, to influence others, and to practice Islamic teachings more effectively and efficiently.To better-know the concept of mujadalah, this account seriously examines some basic assumption corceming kaifiyat mujadalah: from its definition, subject matters, meanings and functions, to its relationship withother scientific efforts. Besides, it also discusses the concept as revealed within Alquran and as found amid the historical realities, its other names, sources, legitimacy, and problems faced by mujadalah. It is clear  throughout the examination that mujadalah is a methode of dakwah that has a so firm argumentative grounds that it is closely related with the intellectual values.